Intimismo e resistência: reflexões sobre os discursos poéticos de Ana Cristina César e Ferreira Gullar / Intimacy and resistance: reflections on Ana Cristina César’s and Ferreira Gullar’s poetical discourses - Bora, Zelia Monteiro; Andrade, Fernando Cézar Bezerra de (Revista de Letras, 2007)
O presente trabalho propõe uma reflexão que relaciona comparativamente os discursos poéticos de Ana Cristina César e Ferreira Gullar, considerados na similaridade do uso de uma linguagem semiótica feminina, em poemas analisados a partir da presença de traços de intimismo e resistência ideológica, que desconstroem os discursos hegemônicos. The changes introduced by the “avant-garde” literary movements were the starting point for the creation of new signs. One of these signs is the feminine semiotic language. The feminine is a mode of language open to male and female poets and writers. Through this mode, it is possible to relate Ana Cristina César’s and Ferreira Gullar’s poetical languages as similar discourse, able to symbolically deconstruct the hegemonic discourses.